2021
DOI: 10.18203/2394-6040.ijcmph20211267
|View full text |Cite
|
Sign up to set email alerts
|

Emerging issues and barriers in access to menstrual hygiene management in a tribal district of India

Abstract: Background: Access to Menstrual Hygiene Management (MHM) remains a critical challenge to Indian women especially in remote areas. The problem of poor availability, acceptance, and affordability of MHM products is further aggravated by negative social construct and environmental concerns. Poor menstrual hygiene is linked to significant morbidity and mortality due to reproductive tract infections (RTIs) and cervical cancer etc.Methods: A campaign “Chuppi Todo” was organized in Udaipur; a tribal district in Rajas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
1
3
1
Order By: Relevance
“…Studies show that national level health programs require an ideological change in their structure for the benefit of the tribal community, and should include health education for better awareness among tribal women. 13,16 The findings in our study contribute to the fact that reproductive health status of women is influenced by demography, socioeconomic factors, cultural factors, education and knowledge factors etc. It is very important to focus on these determinants of health, in order to strengthen programmes by the government to improve reproductive health state of marginalised population like tribal women.…”
Section: Discussionsupporting
confidence: 54%
“…Studies show that national level health programs require an ideological change in their structure for the benefit of the tribal community, and should include health education for better awareness among tribal women. 13,16 The findings in our study contribute to the fact that reproductive health status of women is influenced by demography, socioeconomic factors, cultural factors, education and knowledge factors etc. It is very important to focus on these determinants of health, in order to strengthen programmes by the government to improve reproductive health state of marginalised population like tribal women.…”
Section: Discussionsupporting
confidence: 54%
“…The use of sanitary pads varies significantly in different tribal communities in India; most females prefer reusable old clothes due to cost factors, availability, and ease of disposal [16][17][18][19][20][21][22][23][24][25]. Contrary to our findings, tribal females residing outside India had a higher pooled prevalence of sanitary pad usage [36].…”
Section: Discussioncontrasting
confidence: 97%
“…In our meta-analysis, there are few studies that report proper disposal of menstrual material after use. The used material was largely thrown indiscriminately, in village ponds, anywhere into a latrine, field, jungle, canal, or bin; flushed down a toilet, buried, wrapped in a newspaper, plastic, or paper; or left on the toilet floor [ 18 , 20 , 24 ]. A few other studies also reported the disposal of MHM in backyard waste for burning [ 34 ].…”
Section: Reviewmentioning
confidence: 99%
“…It is a set of guidelines whose operational uses are humans adapting to and dealing with specific environments [ 37 ]. The sanitation development problem is a socio-cultural challenge [ 38 , 39 , 40 , 41 ]. The cause is the community behavior accustomed to defecating in any place and throwing garbage into the river [ 42 ].…”
Section: Discussionmentioning
confidence: 99%